Ethics and epidemics - Balint, John. (Amsterdam ; Boston : Elsevier, 2006)
"The Advances in Bioethics" series is devoted to publishing collections of original papers and multi-authored volumes that advance the field of bioethics either by exploring new areas, or by taking new approaches to traditional areas. Although the series is published in English, its scope is international, and manuscripts are welcome from authors throughout the world. Divided into three sections this volume covers: Human Rights, Public Safety, and Public Policy; Practitioner Responsibilities During Times of Epidemics; Global Dimensions of Epidemics - each chapter in the book goes in depth to discuss the issues surrounding the topic in question and combines a theoretical thought process with practical application.
Introduction to ethics and epidemics / John Balint, Martin Strosberg, Sean Philpott, Robert Baker -- The statue of security: human rights and post-9/11 epidemics / George J. Annas -- Quarantine and civil liberties / Paul J. Edelson -- The 2003 SARS outbreak in Canada: legal and ethical lessons about the use of quarantine / Nola M. Ries -- Can mandatory vaccination of health care professionals during an Influenza pandemic ever be justified? / Jaro Kotalik -- Medical ethics and epidemics: a historical perspective / Robert Baker -- Physician professionalism and preparing for epidemics: challenges and opportunities / Matthew K. Wynia, Jacob F. Kurlander, Shane K. Green -- Doctors, duties, and dangers: the reasonable physician and contagious populations / Chalmers C. Clark -- Ethically justified limits on the obligations of physicians and health care organizations in response to epidemics and bioterrorism / Laurence B. McCullough -- Ethics and epidemics in the developing world: the case of AIDS in Africa: treatment challenges / Angela Wasunna, Daniel W. Fitzgerald -- Under what conditions is clinical research in developing countries exploitative? a framework for assessing exploitation in mutually advantageous transactions / Angela Ballantyne -- A winter's tale: bioethics confronts Avian Flu / Laurie Zoloth, Stephen Zoloth.
"Based upon the proceedings of a conference on ethics and epidemics hosted in March 2004 by Albany Medical College and the Graduate College of Union University ..." -- Introd.
Includes bibliographical references.
Description based on print version record.
Keywords: Epidemiology -- Moral and ethical aspects -- Congresses; Medical ethics -- Congresses; Communicable diseases -- Treatment -- Moral and ethical aspects -- Congresses; Medical ethics & professional conduct; Epidemiology & medical statistics; Medical -- Epidemiology; Medical -- Ethics